If the 2q is raised to the second power the answer is 2q^2+7q+3
Answer:
Kate = 52 seconds, Alexia = 58 seconds, Trina = 49 seconds
Step-by-step explanation:
A = K + 6
T = K - 3
K + A + T = 2 min 39 sec or 159 sec
K + (K + 6) + (K - 3) = 159sec
3K + 3 = 159sec
3K = 156sec
K = 52 sec
A = 52 + 6 = 58 sec
T = 52 - 3 = 49 sec
![I=5\int \frac{cos^{4}\theta }{sin\theta }\times cos\theta d\theta \\\\I=5\int \left ( 1-sin^{2}\theta \right )^{2}\times \frac{cos\theta }{sin\theta }d\theta \\put\ \sin\theta =t\\\\dt=cos\theta d\theta \\\\I=5\int\frac{t^{4}+1-2t^{2}}{t}dt\ \ \ \ \ \ \ \ \ \ \because (a-b)^2=a^2+b^2-2ab\\\\I=5\left ( \int t^{3}dt + \int \frac{1}{t} -2\int t \right )dt](https://tex.z-dn.net/?f=I%3D5%5Cint%20%5Cfrac%7Bcos%5E%7B4%7D%5Ctheta%20%7D%7Bsin%5Ctheta%20%7D%5Ctimes%20cos%5Ctheta%20d%5Ctheta%20%5C%5C%5C%5CI%3D5%5Cint%20%5Cleft%20%28%201-sin%5E%7B2%7D%5Ctheta%20%20%5Cright%20%29%5E%7B2%7D%5Ctimes%20%5Cfrac%7Bcos%5Ctheta%20%7D%7Bsin%5Ctheta%20%7Dd%5Ctheta%20%5C%5Cput%5C%20%5Csin%5Ctheta%20%3Dt%5C%5C%5C%5Cdt%3Dcos%5Ctheta%20d%5Ctheta%20%5C%5C%5C%5CI%3D5%5Cint%5Cfrac%7Bt%5E%7B4%7D%2B1-2t%5E%7B2%7D%7D%7Bt%7Ddt%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5Cbecause%20%28a-b%29%5E2%3Da%5E2%2Bb%5E2-2ab%5C%5C%5C%5CI%3D5%5Cleft%20%28%20%5Cint%20t%5E%7B3%7Ddt%20%2B%20%5Cint%20%5Cfrac%7B1%7D%7Bt%7D%20-2%5Cint%20t%20%5Cright%20%29dt)
by using the integration formula
we get,
![\\I=5\left ( \frac{t^{4}}{4} +logt -t^{2}\right )\\\\I=\frac{5}{4}t^{4}+5\log t-5t^{2}+c](https://tex.z-dn.net/?f=%5C%5CI%3D5%5Cleft%20%28%20%5Cfrac%7Bt%5E%7B4%7D%7D%7B4%7D%20%2Blogt%20-t%5E%7B2%7D%5Cright%20%29%5C%5C%5C%5CI%3D%5Cfrac%7B5%7D%7B4%7Dt%5E%7B4%7D%2B5%5Clog%20t-5t%5E%7B2%7D%2Bc)
now put the value of t=\sin\theta in the above equation
we get,
![\int 5\cot^5\theta \sin^4\theta d\theta=\frac{5}{4}sin^{4}\theta+5\log \sin\theta - 5sin^{2} \theta+c](https://tex.z-dn.net/?f=%5Cint%205%5Ccot%5E5%5Ctheta%20%5Csin%5E4%5Ctheta%20d%5Ctheta%3D%5Cfrac%7B5%7D%7B4%7Dsin%5E%7B4%7D%5Ctheta%2B5%5Clog%20%5Csin%5Ctheta%20-%205sin%5E%7B2%7D%20%5Ctheta%2Bc)
hence proved
![z=f(x(u,v),y(u,v)),\begin{cases}x(u,v)=2u+v^2\\y(u,v)=3u-v\end{cases}](https://tex.z-dn.net/?f=z%3Df%28x%28u%2Cv%29%2Cy%28u%2Cv%29%29%2C%5Cbegin%7Bcases%7Dx%28u%2Cv%29%3D2u%2Bv%5E2%5C%5Cy%28u%2Cv%29%3D3u-v%5Cend%7Bcases%7D)
We're given that
and
, and want to find
.
By the chain rule, we have
![\dfrac{\partial z}{\partial v}=\dfrac{\partial z}{\partial x}\dfrac{\partial x}{\partial v}+\dfrac{\partial z}{\partial y}\dfrac{\partial y}{\partial v}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20z%7D%7B%5Cpartial%20v%7D%3D%5Cdfrac%7B%5Cpartial%20z%7D%7B%5Cpartial%20x%7D%5Cdfrac%7B%5Cpartial%20x%7D%7B%5Cpartial%20v%7D%2B%5Cdfrac%7B%5Cpartial%20z%7D%7B%5Cpartial%20y%7D%5Cdfrac%7B%5Cpartial%20y%7D%7B%5Cpartial%20v%7D)
and
![\dfrac{\partial x}{\partial v}=2v](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20x%7D%7B%5Cpartial%20v%7D%3D2v)
![\dfrac{\partial y}{\partial v}=-1](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20y%7D%7B%5Cpartial%20v%7D%3D-1)
Then
![\dfrac{\partial z}{\partial v}(1,2)=\dfrac{\partial z}{\partial x}(6,1)\dfrac{\partial x}{\partial v}(1,2)+\dfrac{\partial z}{\partial y}(6,1)\dfrac{\partial y}{\partial v}(1,2)](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20z%7D%7B%5Cpartial%20v%7D%281%2C2%29%3D%5Cdfrac%7B%5Cpartial%20z%7D%7B%5Cpartial%20x%7D%286%2C1%29%5Cdfrac%7B%5Cpartial%20x%7D%7B%5Cpartial%20v%7D%281%2C2%29%2B%5Cdfrac%7B%5Cpartial%20z%7D%7B%5Cpartial%20y%7D%286%2C1%29%5Cdfrac%7B%5Cpartial%20y%7D%7B%5Cpartial%20v%7D%281%2C2%29)
(because the point
corresponds to
)
![\implies\dfrac{\partial z}{\partial v}(1,2)=3\cdot2\cdot2+(-1)\cdot(-1)=\boxed{13}](https://tex.z-dn.net/?f=%5Cimplies%5Cdfrac%7B%5Cpartial%20z%7D%7B%5Cpartial%20v%7D%281%2C2%29%3D3%5Ccdot2%5Ccdot2%2B%28-1%29%5Ccdot%28-1%29%3D%5Cboxed%7B13%7D)